2020
DOI: 10.3390/ma13112506
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Studies on Centrifugal MQL-CCA Method of Applying Coolant during Internal Cylindrical Grinding Process

Abstract: This paper describes simulation studies regarding the application of the centrifugal minimum quantity lubrication (MQL) method simultaneously with the delivery of a compressed cooled air (CCA) stream in the internal cylindrical grinding process. The idea of a new hybrid cooling and lubrication method connecting centrifugal (through a grinding wheel) lubrication by MQL with a CCA stream is described. The methodology of computational fluid dynamics (CFD) simulation studies, as well as the results of numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The results of numerical simulations [126] and experimental research [127] have shown that the developed hybrid method allows for about 2.7 times longer wheel life in comparison with the results obtained under flooded cooling or centrifugal MQL conditions. The wheel life was as much as 8 times longer in comparison with the wheel life under SSP only delivering or dry grinding conditions.…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 88%
See 2 more Smart Citations
“…The results of numerical simulations [126] and experimental research [127] have shown that the developed hybrid method allows for about 2.7 times longer wheel life in comparison with the results obtained under flooded cooling or centrifugal MQL conditions. The wheel life was as much as 8 times longer in comparison with the wheel life under SSP only delivering or dry grinding conditions.…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 88%
“…They were the motivation to undertake work aimed at applying the CAOM method also in the process of internal cylindrical grinding characterized by limited space in the contact zone of the grinding wheel with the workpiece. This is how the method was developed in which a patented centrifugal air-oil aerosol delivering through the grinding wheel [124] was combined while simultaneous incorporating the CAG nozzle into the system [125][126][127].…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim was to determine the most favorable geometrical and kinematic parameters of the process in terms of the flow of cooling and lubricating media (air-oil aerosol and CCA), as well as heat exchange. The conditions and results of these simulations were described in detail in the paper [65]. The most advantageous of the variants analyzed in the simulation studies was then selected for experimental research, in which the service life of the grinding wheels was determined with reference to four methods of cooling and lubricating the machining zone.…”
Section: Setup Of Centrifugal Mql-cca Methods Of Coolant Delivery During Internal Cylindrical Grinding Processmentioning
confidence: 99%
“…The conditions and results of these simulations were described in detail in the paper [65]. The most advantageous of the variants analyzed in the simulation studies was then selected for experimental research, in which the service life of the grinding wheels was determined with reference to four methods of cooling and lubricating the machining zone.…”
Section: Experimental Research On the Internal Cylindrical Grinding Processmentioning
confidence: 99%